2008
DOI: 10.1037/0893-164x.22.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Movie smoking exposure and smoking onset: A longitudinal study of mediation processes in a representative sample of U.S. adolescents.

Abstract: The authors tested 2 mechanisms for the relation of movie smoking exposure with onset of cigarette smoking in adolescence. Longitudinal data with 8-month follow-up were obtained from a representative sample of 6,522 U.S. adolescents, ages 10-14 years. Structural modeling analysis based on initial nonsmokers, which controlled for 10 covariates associated with movie exposure, showed that viewing more smoking in movies was related to increases in positive expectancies about smoking and increases in affiliation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 65 publications
6
50
0
2
Order By: Relevance
“…Although psychosocial mechanisms that mediate this association have been explored Wills et al, 2007Wills et al, , 2008, research has not yet examined whether the way that smoking is portrayed in movies affects its influence on adolescent smoking. Portrayals of smoking to relax, appear rebellious, and facilitate social interactions are common in movies , and adolescents who believe that smoking will help serve such motives are more generally at greater risk of smoking (Johnson et al, 2003;Wills et al, 1999Wills et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Although psychosocial mechanisms that mediate this association have been explored Wills et al, 2007Wills et al, , 2008, research has not yet examined whether the way that smoking is portrayed in movies affects its influence on adolescent smoking. Portrayals of smoking to relax, appear rebellious, and facilitate social interactions are common in movies , and adolescents who believe that smoking will help serve such motives are more generally at greater risk of smoking (Johnson et al, 2003;Wills et al, 1999Wills et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Similar longitudinal effects were found for smoking. In a sample of 2,614 children in Grades 5-8, Wills, Sargent, Stoolmiller, Gibbons, and Gerrard (2008) found that exposure to smoking in movies predicted smoking behavior and inclinations 18 months later (see also TitusErnstoff, Dalton, Adachi-Meija, Longacre, & Beach, 2008). Other longitudinal studies have found similar effects for exposure to sex on television and initiation of risky sexual behavior (Collins, Elliott, Berry, Kanouse, Kunkel, Hunter, & Miu, 2004) and for early exposure to alcohol marketing and underage drinking (Collins, Ellickson, McCaffrey, & Hambarsoomians, 2007; see also Ellickson et al, 2005).…”
Section: Correlational Studies: Cross-sectional and Longitudinal Resementioning
confidence: 99%
“…Regarding covariates, peer drinking was measured only at follow-up; however, that should result in an overestimation of its effect, because peer substance use is a proximal risk factor and can even be viewed as a mediating variable (Dal Cin et al, 2009;Wills et al, 2007Wills et al, , 2008. We also did not assess parental alcohol use or home alcohol access.…”
Section: Changes In R-movie Restrictions and Trying Drinkingmentioning
confidence: 99%